Pengembangan Literasi Budaya dan Kewargaan di Keluarga - Annisa Laela Putri; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
Easy access to information allows the entry of foreign cultures which sometimes do not match local cultural values. Children become more aware of foreign cultures because a lot of information is spread from their cell phones. The world is increasingly globalizing, but knowing and understanding local culture is an important thing in inheriting cultural values ​​and local wisdom. In the midst of the pressure of the influx of foreign cultures that is difficult to stop, it is a challenge for parents to ensure that their children understand their nation's culture. For this reason, the family plays an important role for children in facing the openness of the Indonesian nation in the era of globalization through cultural literacy. The aim of this research is to find out the role of the family in cultural literacy and citizenship. The method used in this research is literature study.